Valorization of Wasted Black Tea as a Low-Cost Adsorbent for Nickel and Zinc Removal from Aqueous Solution - Amirhossein Malakahmad; Sandee Tan; Saba Yavari (Journal of Chemistry)
Characteristics and efficiency of wasted black tea (WBT) were investigated as a low-cost sorbent in removal of Ni2+ and Zn2+ ions from aqueous solution. Initial findings showed WBT potential to be applied as an effective sorbent due to high concentrations of carbon and calcium and high porosity and availability of functional groups. Sorption dynamics were studied with varying pH, contact time, and adsorbent dose. Maximum percentages of metal ions removal were recorded at pH 5, contact time 250 min, and 20 g/L of adsorbent concentration. Binary metal sorption studies showed that Ni2+ and Zn2+ do not compete with each other for available sorption sites, so the adsorption trend in binary system appears similar to monocomponent metal adsorption. Evaluation of the isotherms confirmed that WBT has high value of adsorption capacity. Sorption data fitted well with both Freundlich and Langmuir models. In the optimum conditions, maximum capacity of WBT could reach up to 90.91 mg-Ni/g adsorbent and 166.67 mg-Zn/g adsorbent. This experiment demonstrated the ability of tea waste as an effective, sustainable, and low-cost adsorbent for removal of the heavy metal ions.